The Authority Guide to PR for Small Businesses : Use the Power of Public Relations and the Media to Reach Your Target Customer and Grow Your Business. - Bustin, Steve (Authority guides., 2017)
This Authority Guide shows you how to grab the headlines (for all the right reasons), reach huge audiences and grow your business by accessing the media to tell your story.